2010
DOI: 10.1348/135910709x429091
|View full text |Cite
|
Sign up to set email alerts
|

The association between regulatory focus and distress in patients with a chronic disease: The moderating role of partner support

Abstract: Active engagement appears to buffer against high distress in patients with a weak promotion focus, while protective buffering and overprotection appear to aggravate distress in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 52 publications
5
22
0
1
Order By: Relevance
“…Promotion focus strategies might act as resources, potentially providing additional resources to cope with threats. Moreover, other results have indicated that there is an intimate relationship between regulatory focus and health outcomes . Overall, our results are consistent with previous studies, which revealed that the regulatory focus affected burnout, in that our study showed that the type of regulatory focus can directly reduce burnout and can indirectly reduce burnout by transformational leadership.…”
Section: Discussionsupporting
confidence: 93%
“…Promotion focus strategies might act as resources, potentially providing additional resources to cope with threats. Moreover, other results have indicated that there is an intimate relationship between regulatory focus and health outcomes . Overall, our results are consistent with previous studies, which revealed that the regulatory focus affected burnout, in that our study showed that the type of regulatory focus can directly reduce burnout and can indirectly reduce burnout by transformational leadership.…”
Section: Discussionsupporting
confidence: 93%
“…One suggestion from research is that, when individuals are socially integrated into their social surroundings, the negative effects of, for instance, a terrorist attack are buffered (Schwarzer, Bowler, & Cone, ) and could help individuals to cope with their negative reaction. Similar results for social support in other domains are demonstrated in other research (e.g., in the health domain: Schokker, Links, Luttik & Hagedoorn, ). Another suggestion is that finding meaning as a result of the experience of a negative event helps to reduce stress levels and fears of future events (Updegraff, Silver, & Holman, ), as it may encourage constructive ways to cope with the negative event.…”
Section: Discussionsupporting
confidence: 90%
“…The negative link that was found between prevention regulatory fit and exhaustion is in the same line with research linking individual prevention focus with emotional exhaustion (Brenninkmeijer et al, 2010) or anxious attachment (Moss, 2009) in employees and distress in chronic patients (Schokker, Links, Luttik, & Hagedoorn, 2010). By experiencing misfit more profoundly, prevention-focused individuals are likely to develop adverse health reactions that are typical for prevention failure (Klenk et al, 2011).…”
Section: Discussionsupporting
confidence: 64%